Partisipasi Masyarakat dalam Pembangunan di Desa Tanah Towa - Malikul Afdal, Andi Ahmad; Syam, Andi Armayudi; Herman, Herman; Sumardi, Sumardi (Journal of Government Insight, 2023)
The village is the government closest to the community and is expected to be able to run the wheels of village administration properly and work closely with the community on the existing development program in the village. Tanah Towa Village, Kajang District, Bulukumba Regency, one of the villages that must also work with the community in involving community participation in village development, community participation in Tanah Towa Village is inseparable from existing problems, on this basis this research focuses on how community participation in Tanah Towa Village Towa in village development, using qualitative research methods, through Keith Davis' participation form indicators, among others, thought participation, labor participation and material participation. The results of this study indicate that community participation in Tanah Towa Village is still lacking in every development program in Tanah Towa Village.